The The Effect of Profitability (Return on Investment) and Financial Risk Against Stock Price Before Covide-19 - Sunaryo, Deni (International Journal of Science, Technology & Management, 2020)
The discussion leads to the effect of profitability of return on investment (ROI) and financial risk on stock prices which shows the inequality of the results of previous studies. Therefore, this study was conducted to determine whether the difference has a relationship between return on investment (ROI) profitability and financial risk to the stock price under study. This research uses automotive industry and spare parts companies in the Southeast Asia Stock Exchange for the 2012-2018 period. The method used was purposive sampling to obtain 10 companies that present complete financial statements, so as many as 70 samples were obtained. The analysis technique used is multiple linear regression analysis, partial test and simultaneous test. The results of the partial study concluded that the profitability of return on investment (ROI) and financial risk have a significant effect on stock prices. The results of the study simultaneously return on investment (ROI) profitability and financial risk has a significance level of 0.001 <0.05 then simultaneously states that profitability return on investment (ROI) and financial risk have a significant effect on stock prices. Future studies are expected to add or replace variables and methodologies of other sub-sectors